Biomimetik pada Bahan Kedokteran Gigi - Atia Nurul Sidiqa (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2013)
Natural phenomena can inspire people to be able to produce new materials effectively and efficiently, especially in biological tissue. The mechanism mimics nature can increase the potential of tools and materials that we use for applications in dentistry in order to easily adapt the physical, mechanical, and biological or biomimetic. The mechanism of dental materials imitate nature has been conducted on the active ingredient of hydroxyapatite coatings on dental implants. The nature imitating nature can produce the best material because it has good biocompatibility. Bioactive materials, such as hydroxyapatite is a dental material that mimics the mechanisms inspired by nature (biomimetic). Biomaterials are currently developing rapidly is ceramic. Ceramic is a material bioinert. One example is the hydroxyapatite ceramic material that can be used as a repair material defect in the bone caused by disease or trauma. Hydroxyapatite (Ca10(PO4) 6(OH)2) is produced from calcium phosphate cement is a biomaterial that has good potential for application in medicine and dentistry, orthopedics and maxillofacial purpose, because it has favorable properties such as good biocompatibility, bioactive, and osteoconductive. This paper describes the various aspects of biomimetic and its application in dentistry